(3UahI GdePgH ef fgGjI GdeWdHs - (3TQa GdOjf CHi SYO YHO Gddg GHf eMeO Hf gHg Gddg Hf CHi YUQhf GdehUdjs ((3CMeO Hf CHj HcQ Hf Ndjd s)
(3ChdgG (B:s
(3HGH GdWdGb HGdMSGH hGdGSJKfGA s
(3BNQgG (B:s
(3BNQ cJGH GdMVGfI s
(3ef fSNI CNQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 - (3U (B309 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1990s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(880) s
Keywords: (3Gdabg GdTGaYjs